1995
DOI: 10.1212/wnl.45.4.724
|View full text |Cite
|
Sign up to set email alerts
|

A population-based study of neonatal seizures in Fayette County, Kentucky

Abstract: This population-based, retrospective cohort study of neonatal seizures included all neonates born to residents of Fayette County, Kentucky, from 1985 to 1989. We ascertained potential cases by computer search of hospital-based medical record systems, Kentucky Center for Health Statistics birth certificate data files, and National Center for Health Statistics multiple-cause-of-death mortality data files. Medical records for potential cases were abstracted, and relevant portions were reviewed independently by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
124
1
6

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(139 citation statements)
references
References 17 publications
8
124
1
6
Order By: Relevance
“…The incidence of clinically diagnosed NSs ranges from 1.5 to 3.5 per 1000 live term born babies. [1][2][3] Because most electrographic seizures in the neonate are subclinical, these figures may underestimate their true incidence. [4][5][6][7] Clinical NSs have been correlated with significant neurological morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of clinically diagnosed NSs ranges from 1.5 to 3.5 per 1000 live term born babies. [1][2][3] Because most electrographic seizures in the neonate are subclinical, these figures may underestimate their true incidence. [4][5][6][7] Clinical NSs have been correlated with significant neurological morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…First, the incidence of seizures is greater in the neonatal period than at any other time of life, and the vast majority of seizures that occur during this period do so within the first week of life. The reported incidence of seizures has varied between 1.8/1,000 and 5.1/1,000 live births, depending on the methodology used and the locale and dates of specific studies (19)(20)(21)(22). Within the groups studied, the incidence of SE may be very high, depending on definition, Scher and colleagues (4) found that 33% of full-term neonates with seizures could be diagnosed with SE, defined by either the occurrence of a single 30-min seizure, the presence of seizures during at least 50% of an EEG recording, or both.…”
Section: Occurrence Of Neonatal Seizuresmentioning
confidence: 99%
“…1 The risk of seizures is highest during the neonatal period, with US population-based studies reporting an incidence of seizures of 1.8 to 5 out of every 1000 live births. [2][3][4] Neonatal seizures are different, in terms of aetiology, semiology, electroencephalographic features, treatment options, and treatment responses, from seizures affecting other age groups. 5 Idiopathic seizures are extremely rare, and most neonatal seizures are symptomatic.…”
mentioning
confidence: 99%
“…5 Idiopathic seizures are extremely rare, and most neonatal seizures are symptomatic. 2,3,5 More than 90% of neonatal seizures are accounted for by hypoxic-ischaemic encephalopathy (HIE), cerebral vascular ischaemia and haemorrhage, cerebral malformation, and infections. Hypoxic-ischaemic encephalopathy is the most common cause of neonatal seizures, with a reported incidence of 1 to 2 per 1000 live births.…”
mentioning
confidence: 99%
See 1 more Smart Citation